Red up-conversion dynamics in Er3+-doped TeO2–ZnO glasses - Cherif, Abdelfatteh; Kanoun, Abdelaziz; Jaba, Nejeh (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Red fluorescence has been obtained under 980 nm excitation in Er3+-doped TeO2–ZnO glasses. The dynamics of the red up-conversion is well explained with the proposed model. The energy transfer processes are predominant.
Optica Applicata, Vol. 40, 2010, nr 1, s. 109-118
Keywords: optyka; tellurite glasses; erbium: Er3+; dynamics of up-conversion